2022
DOI: 10.3390/ijms24010082
|View full text |Cite
|
Sign up to set email alerts
|

The Normobaric Oxygen Paradox—Hyperoxic Hypoxic Paradox: A Novel Expedient Strategy in Hematopoiesis Clinical Issues

Abstract: Hypoxia, even at non-lethal levels, is one of the most stressful events for all aerobic organisms as it significantly affects a wide spectrum of physiological functions and energy production. Aerobic organisms activate countless molecular responses directed to respond at cellular, tissue, organ, and whole-body levels to cope with oxygen shortage allowing survival, including enhanced neo-angiogenesis and systemic oxygen delivery. The benefits of hypoxia may be evoked without its detrimental consequences by expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 82 publications
(114 reference statements)
1
9
0
Order By: Relevance
“…However, former studies concluded that this response followed the vasoconstriction and increased blood pressure induced by hyperoxia. These counterintuitive findings support the "hyperoxia-hypoxia" paradox, where increased O 2 from a hyperoxic exposure may induce a hypoxic response that manifests through different mechanisms [50][51][52]. Interestingly though, while the physiological effects of hyperoxia appear negative, several studies previously reported enhanced cognitive outcomes following acute hyperoxic exposures of 30% to 100% O 2 .…”
Section: Ans Response To Hyperoxiasupporting
confidence: 54%
“…However, former studies concluded that this response followed the vasoconstriction and increased blood pressure induced by hyperoxia. These counterintuitive findings support the "hyperoxia-hypoxia" paradox, where increased O 2 from a hyperoxic exposure may induce a hypoxic response that manifests through different mechanisms [50][51][52]. Interestingly though, while the physiological effects of hyperoxia appear negative, several studies previously reported enhanced cognitive outcomes following acute hyperoxic exposures of 30% to 100% O 2 .…”
Section: Ans Response To Hyperoxiasupporting
confidence: 54%
“…Inflammation may be influenced by fiO 2 level, as reported by some authors investigating subjects exposed to hypoxia that showed pulmonary edema caused by inflammatory markers release, including interleukin-6 (IL-6) and protein C-reactive (CRP) [ 24 , 25 , 26 ]. To adapt body tissues to hypoxia, hypoxia-inducible factors (HIFs), a family of heterodimers that constitute a transcription complex that is stabilized by hypoxia [ 26 ] or a return from hyperoxia [ 27 , 28 , 29 , 30 ], are activated to coordinate several transcriptional pathways to optimize metabolic and vascular functions toward low fiO 2 [ 31 ]. Furthermore, HIFs are controlled by prolyl hydroxylase domain (PHD) proteins, a class of “O 2 sensors” that are involved in HIF level regulation and O 2 homeostasis [ 32 ].…”
Section: Oxy-inflammation-related Mechanisms and Outcomesmentioning
confidence: 99%
“…Hyperoxic-hypoxic paradox has been reported in previous therapeutic uses of oxygen and the effect has been extensively discussed in literature ( Balestra and Kot, 2021 ; Balestra et al, 2023 ). Hyperoxic-normoxic exposure has been shown to exhibit hematopoietic functions and results in the production of erythropoietin and increased levels of haemoglobin ( Salvagno et al, 2022 ). Intermittent conditions of oxidative stress can arise during situations like physical exercise which can generate the similar effect in the form of eliciting antioxidant protection and erythropoietin production ( Revelli et al, 2013 ; Fratantonio et al, 2021 ).…”
Section: Effect Of Hbot On Aging and Cellular Regenerationmentioning
confidence: 99%